Writing and Political Engagement: The Figure of the Intellectual in Maurice Blanchot - Dionizio, Mayara; Rodrigues, Erika (Eddissi Languages Journal, 2026)
By analyzing the different modulations that constitute the figure of the “intellectual” in Maurice Blanchot’s thought, this article aims to understand the singular and yet inseparable movements involved in the relationship between “writing” and “political commitment.” Through a reading of Blanchot’s work from the 1930s to the 1980s, we explore Blanchotian approaches to this figure. First, that of the writer withdrawn into his “ivory tower,” a conception inherited from a certain reading of Mallarmé; then, the figure of the intellectual “imprisoned” (embastillé), for whom Sade becomes the tutelary model of a literature that transgresses all power; and finally, the anonymous intellectual, engaged in the collective experiences of the 1960s and especially of May ‘68. Within the framework of these theoretical developments, we consider Blanchot’s political radicalization from the 1950s onward, particularly through his anti-colonialist commitment, his participation in drafting the Manifeste des 121, and his experience within the “Comité d’action étudiants-écrivains”, all of which profoundly marked his conception of the relationship between writing and politics. This trajectory leads us to Blanchot’s elaborations during the 1980s, as found in La communauté inavouable (1983) and Les intellectuels en question (1984), where this question consolidates into a radical ethical exigency that compels the figure of the intellectual.